Follow-up in non-muscle-invasive bladder cancer-International Bladder Cancer Network recommendations - Kassouf, Wassim; Traboulsi, Samer L.; Schmitz-Draeger, Bernd; Palou, Joan; Witjes, Johannes Alfred; van Rhijn, Bas W. G.; Grossman, Herbert Barton; Kiemeney, Lambertus A.; Goebell, Peter; Kamat, Ashish M. (Urologic Oncology-Seminars and Original Investigations, 2016)
Non-muscle-invasive bladder cancer (NMIBC) comprises a wide spectrum of tumors with different behaviors and prognoses. It follows that the surveillance for these tumors should be adapted according to the risks of recurrence and progression and should be dynamic in design.Medline search was conducted from 1980 to 2016 using a combination of MeSH and keyword terms. The highest available evidence was reviewed to define different risk groups in NMIBC. The performance of different follow-up tools such as urine cytology, cystoscopy, and upper tract imaging in detecting bladder carcinoma was assessed. Different commercially available urinary markers were investigated to determine whether such markers would contribute to the surveillance of patients with NMIBC. A follow-up scheme based on the early evidence is proposed.A risk-based approach is paramount. Cystoscopy and cytology are recommended to be done at 3 months following transurethral resection of bladder tumor. For low-risk tumors, annual cystoscopy alone is sufficient; no upper tract evaluations or cytology is needed except at diagnosis. High-risk tumors should be followed up with a more intense schedule: cystoscopy every 3 months for 2 years, 6 months for 2 years, and then annually, with cytology at frequent intervals, and imaging for upper tract evaluation at 1 year and then every 2 years. Intermediate-risk tumors should be subclassified as per the International Bladder Cancer Group recommendations and when associated with 3 or more of the following findings (multiple tumors, size>=3cm, early recurrence<1 year, frequent recurrences>1 per year) then a surveillance strategy similar to that of high risk should be followed. Several urine markers were more sensitive than cytology in the detection of NMIBC; however, these tests are still costly, require specialized laboratories, and do not replace cystoscopy. Until better and cheaper markers are available, their routine use has not been integrated in the follow-up recommendation of current guidelines.Surveillance of NMIBC should follow a risk-adapted approach, with a combination of cystoscopy, cytology, and upper tract imaging. The aim of this approach is to minimize the therapeutic burden of a disease with high recurrence rates without missing progressing tumors. When designing a diagnostic pathway, first-line diagnostic imaging tests should have high sensitivity to ensure disease positives are included in the test population for further investigation. Second-line investigations should be highly specific, to ensure false-positives are minimized.
EVALuna2:16354